2022
DOI: 10.1017/ash.2021.254
|View full text |Cite|
|
Sign up to set email alerts
|

Evaluation of prevalance and risk factors for bloodstream infection in severe coronavirus disease 2019 (COVID-19) patients

Abstract: Objectives: In this study, we sought to determine the prevalence of bloodstream infection (BSI) in severe coronavirus disease 2019 (COVID-19) patients and to determine the risk factors of BSI in critical COVID-19 patients. Design: Retrospective, descriptive study between March 2020 and January 2021. Setting: An 1,007-bed university hospital. Participants: Patients who were hospitalized due to severe COVID-19 disease and had an aerobic blood culture tak… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
1
1
0
Order By: Relevance
“…Whether the increase in Enterococcal bacteremia is due to systemic inflammation, or gut translocation due to the microbiome dysbiosis observed in COVID-19 patients, frequent concomitant use of ceftriaxone, or some still unknown mechanism responsible, remains to be explored [ 47 , 48 ]. Nosocomial infections with resulting CoNS bacteremia have been previously described, and they exhibited similarities to the findings in our study [ 8 , 30 ]. Higher rates of Staphylococcus aureus and its mortality in COVID-19 patients were also previously reported.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Whether the increase in Enterococcal bacteremia is due to systemic inflammation, or gut translocation due to the microbiome dysbiosis observed in COVID-19 patients, frequent concomitant use of ceftriaxone, or some still unknown mechanism responsible, remains to be explored [ 47 , 48 ]. Nosocomial infections with resulting CoNS bacteremia have been previously described, and they exhibited similarities to the findings in our study [ 8 , 30 ]. Higher rates of Staphylococcus aureus and its mortality in COVID-19 patients were also previously reported.…”
Section: Discussionsupporting
confidence: 90%
“…An earlier report from Giacobbe et al turned researchers’ attention to the association between the use of steroids and other immunomodulatory therapy, with a higher risk of BSI among ICU patients. The following studies suggested more opposite than confirmative findings, leaving possible associations inconclusive [ 10 , 24 , 29 , 30 , 31 , 32 ]. Studies described the association between the use of glucocorticoids and the occurrence of BSI, but no study explored the association between dose strength and BSI, on which we report here.…”
Section: Discussionmentioning
confidence: 99%